Feasibility of a fourth ventriculopleural shunt for diversion of an isolated fourth ventricle: A technical note - Lewis, Courtney; Chang, Ki-Eun; Bakhsheshian, Joshua; Strickland, Ben; Pham, Martin (Asian Journal of Neurosurgery, 2018)
Isolated fourth ventricle syndrome is an uncommon entity due to obstruction of both inlet and outflow foramina. The resulting mass effect from the progressively expanding fourth ventricle may cause symptoms from both cerebellar and brainstem compression. Although a variety of treatment modalities have been advocated for this condition, an in-depth description of placement of a fourth ventriculopleural (VPL) shunt from a single-stage prone approach has not yet been published in the literature. We describe here a case of successful placement of a fourth VPL shunt in a 22-year-old female with a history of a prior posterior fossa pilocytic astrocytoma resection who presented with symptomatic isolated fourth ventricular hydrocephalus
Keywords: Fourth ventricle; hydrocephalus; ventriculoperitoneal shunt; ventriculopleural shunt